Plan administrativo financiero para el crecimiento sostenible de la microempresa de distribución de productos de oficina y fotográfico “forte vivitar” - Zambrano Molina, Jaime Oswaldo (2011)
Today there to find an effective way of getting the right money management, but very few people who plan the most efficient way to spend it or invest, the companies also are constantly in search of good financial planning, and further calls SMEs small and medium companies need professionals who propose new ideas and strategies. Every business needs at the present time undergo a process of continuous improvement for the purpose of increasing their competitive levels, generating new business, reducing costs and increasing their profitability. Especially in times like the present where they are forced to reduce costs or yes in order to keep the rates of return. With this background is that this research study is part of the analysis of one of the Ecuadorian geography. The province of Los Ríos and specifically the Canton Quevedo. FORTE VIVITAR distributor is dedicated to selling and marketing items: bazaar, office, photo, students from other materials, and its scope ranges from the city of Quevedo and covers the nearby counties of the Province as good faith, the joint La Mana, and Valencia. Stationery and bookstore are located next to the bridge Velasco Ibarra, due to the influx of clients has made this financial management plan, the same proved to be technically and economically feasible, as the five-year projections, with reference to a interest rate of 12% applied to capital and an opportunity rate of 12%, resulting in a Net Present Value (NPV) positive $ 778,963.08. The initial investment amounts to a total of $ 30,627.05 to recover them over a period of 1 year. With regard to financial analysis, with its most representative parameter is the Internal Rate of Return (IRR) this gives a figure of 49.32%, exceeding 12% chance .......